Population-based comparative survival analysis of surgery with or without adjuvant radiotherapy and non-operative primary radiotherapy in patients with early-stage oral tongue squamous cell carcinoma. - Yu Jin Lim (Public Library of Science (PLoS), 2021)
Purpose Although recent clinical guidelines do allow primary radiotherapy for selected patients with early-stage oral tongue cancer, there has been little knowledge on the treatment outcomes of non-operative radiotherapy using modern treatment techniques. This study evaluated recent prognostic differences between primary radiotherapy and surgical resection in T1‒2N0 oral tongue squamous cell carcinoma. Methods Patients diagnosed with T1‒2N0 oral tongue squamous cell carcinoma were identified from the Surveillance, Epidemiology, and End Results database. After propensity score matching, the disease-specific survival of primary radiotherapy and surgery was compared. Results From a total of 8,458 patients initially identified, we defined matched cohorts: cohort A, comparing surgery alone vs. primary radiotherapy (n = 230 vs. 230), and cohort B, comparing surgery plus adjuvant radiotherapy vs. primary radiotherapy (n = 230 vs. 230). The 7-year disease-specific survival rates were 77% vs. 35% (cohort A) and 65% vs. 35% (cohort B) (P < 0.001 for all comparisons). Primary radiotherapy was independently associated with worse disease-specific survival in both cohorts A (hazard ratio 4.06; 95% confidence interval 2.53‒6.52) and B (hazard ratio 2.81; 95% confidence interval 1.96‒4.04). Time-course hazard rate function plots showed a distinct short-term risk increment in disease-specific mortality in the primary radiotherapy group. Conclusion In the contemporary treatment era, the use of radiotherapy as a definitive treatment resulted in an inferior prognosis in patients with T1‒2N0 oral tongue squamous cell carcinoma. The present population-based data suggest that primary radiotherapy cannot be used as an alternative to surgical management and it needs to be avoided as much as possible in early-stage tumors.